“Thriving through Reflecting”: Current Perspective on Teacher Professional Development Research in Asia Context - Krismalita Sekar Diasti; Kuswandono, Paulus (JET (Journal of English Teaching), 2020)
Reflective practice has long gained more spotlight from researchers in the education realm, particularly for promoting teachers’ professional development (TPD). Generally speaking, reflective practice provides abundant merit for teachers, namely, evaluating teachers’ teaching quality, enhancing teachers’ professional skills, and guiding teachers in their professional development. This study aims to present how reflective practice assists English teacher professional development in the Asian context. To discover how reflective practice promotes teacher professional development, the researchers analyzed several research journal articles using a document analysis method. The current contributions of reflective practice present the significance of reflective practice. It involves why and how English teachers should employ the reflective practice in their daily teaching processes. This study provides future research direction as well, specifically on how to equip teachers to become reflective practitioners in their teaching practices, how to provide a supportive environment for reflective practitioners, and how to enhance the implementation of reflective practice through online platforms. Keywords: reflection, reflective practice, reflective practitioner, collaborative reflective practice